2018
DOI: 10.12788/ajo.2018.0043
|View full text |Cite
|
Sign up to set email alerts
|

Open vs Percutaneous vs Arthroscopic Surgical Treatment of Lateral Epicondylitis: An Updated Systematic Review

Abstract: This study was performed to compare outcomes of open, arthroscopic, and percutaneous surgical techniques for lateral epicondylitis. We searched PubMed (MEDLINE) for literature published between January 1, 2004 and May 23, 2015 using these key words: lateral epicondylitis AND (surgery OR operative OR surgical OR open OR arthroscopic OR percutaneous). Meta-analyses were performed for outcomes reported in 3 studies using 2-sample and 2-proportion Z-tests. Thirty-five studies including 1640 elbows (1055 open, 401 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
1
12
1
6
Order By: Relevance
“…Both open surgical treatment and arthroscopic surgical treatment of lateral epicondylitis have been described and are successful. However, open techniques for surgical treatment of lateral epicondylitis have shown a higher rate of pain-free outcomes compared with arthroscopic techniques 15 . An open approach could potentially pose a higher risk of infection as well as more prominent scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Both open surgical treatment and arthroscopic surgical treatment of lateral epicondylitis have been described and are successful. However, open techniques for surgical treatment of lateral epicondylitis have shown a higher rate of pain-free outcomes compared with arthroscopic techniques 15 . An open approach could potentially pose a higher risk of infection as well as more prominent scarring.…”
Section: Discussionmentioning
confidence: 99%
“…However, these outcomes should also be viewed from the perspective of spontaneous complaint response within the first 12 months and the potential risks of surgery. Since surgery does not produce good results in 5 – 20% of cases, the indication for surgery must be very strict and differentiated 141 , 142 , 143 , 144 .…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…The main characteristics of the included SRs were presented in table 2.Among the included studies, there were 15 in China and 22 in English, among which 2 in China were actually the same study.The one with the most complete description was chosen for evaluation.Twenty-nine of the studies included were randomized controlled trials, and 21 were assessed for bias using Cochrane's risk bias assessment tool.Seven was assessed using the Jadad scale, and three were assessed using the PEDro score.Ten literature was reviewed systematically, and 27 were meta-analyzed.Interventions, 12 articles used acupuncture, 4 using the shock wave therapy, 14 with non-surgical therapy, including platelet rich plasma, botulinum toxin injection, autologous blood injection, corticosteroid injections, etc.3 article adopting physical therapy, 4 by operation therapy.See Table 2 for full details. They all employed the PICO approach (population, intervention, control group, and outcome) as an organizing framework for establishing study questions.Most of the included studies adopted the elementary rule of PICO, including 5 non-random, cohort and case-control studies, and the rest were included in RCT.Only 1 article [54] provides protocol registration, and the rest do not provide protocol registration or publication before commencement of the review (AMSTAR2 Item 2).Two SRs [38,44] described the reasons for the type of included study, while none of the others described the reasons for the type of included study(AMSTAR2 Item 3).Only one review [48] had conducted a comprehensive literature search.One review [53] only retrieves one database, which is not inclusive enough(AMSTAR2 Item 4).In two reviews [41,44] authors had not performed study selection and data extraction in duplicate.None of the reviews provided a complete list of potential related studies and reasons for excluding each(AMSTAR2 Item 7).Thirty seven reviews partly provided characteristic information of their included studies.Three SRs [35,41,53] did not evaluate the risk of the included studies, while the rest of them evaluated the quality of the included literature with different scales.Three SRs [23,32,54] had reported funding sources for the included studies and whether there is a con ict of interest between the included studies, while the rest are not reported.Twelve reviews [22, 27-28, 29-30, 38-39, 41, 43, 45-47] applied meta-analytical methods appropriately, explaining factors for xed or random effects model selection and methods used for heterogeneity investigation.Eleven reviews [32,35,37,42,44,50,…”
Section: 2description Of the Included Reviewsmentioning
confidence: 99%